Extreme reduction of thermal conductivity by embedding Al2O3 nanoparticles into single-crystalline Bi nanowires. (1st September 2017) - Roh, Jong Wook; Ham, Jinhee; Kim, Jeongmin; Moon, Hongjae; Kim, Hyun Sik; Lee, Wooyoung
Abstract: Al2 O3 nanoparticles-embedded single-crystalline Bi nanowires were successfully synthesized without using any templates via the spontaneous growth of Bi thin films covered with Al2 O3 nanoparticles. It is experimentally confirmed that Al2 O3 nanoparticles were embedded into the single-crystalline Bi nanowires by using the high-resolution transmission electron microscopy and energy dispersive X-ray spectrometry. The temperature-dependent thermal conductivities of individual Al2 O3 nanoparticles-embedded single-crystalline Bi nanowires were measured directly using suspended micro-devices. The thermal conductivities of the Al2 O3 nanoparticles-embedded Bi nanowires were found to be extremely low compared with those of pure Bi nanowires of similar diameters. Moreover, the thermal conductivity of the Al2 O3 nanoparticles-embedded Bi nanowires was not size-dependent, i.e., it did not vary for nanowires with significantly different diameters. This result suggests that the phonon-boundary scattering is not the dominant phonon scattering mechanism in these systems while the phonon-boundary scattering is dominant in the pure single-crystalline nanowires. From the experimental measurements and theoretical calculation, these drastic reduction and unique tendency in the thermal conductivities of Al2 O3 nanoparticles-embedded Bi nanowires were explained by the combined effect of the phonon-boundary scattering and impurity scattering occurring between the embedded Al2 O3 nanoparticles and Bi matrix. Graphical abstract: